Zakat, infaq, shadaqah, and waqf using financial technology: Millennial generation perspective - Nur Aisyah Indarningsih; Muhammad Agus Futuhul Ma'wa; Muh. Noval Waliyuddinsyah (Center for Islamic Economics and Development Studies [P3EI], 2023)
Purpose – This research is to study Zakat, Infak, Shadaqah, and Waqf (ZISWAF) through fintech for the millennial generation, considering the enormous potential of the millennial generation in Indonesia. Assisted by adopting and modifying the theories of Theory of Planned Behavior (TPB) and Unified Theory of Acceptance and Use of Technology (UTAUT).Methodology – The approach used in this research is quantitative, with primary data as the data type. The data analyst used is in the form of SEM-PLS, assisted by adopting and modifying the theories of the TPB and the UTAUT.Findings – The results show that millennial intentions to make ZISWAF payments using fintech are not affected by behavioral control, but subjective norms and performance expectations greatly impact individual attitudes. Then, in making ZISWAF payments using fintech for the millennial generation, business expectations significantly impact individual intentions. At the same time, performance expectations, facilitation conditions, and individual attitudes do not affect individual intentions. The final results show that personal views do not moderate the relationship between subjective norms, perceptions of behavioral control, and performance expectations on individual intentions to make ZISWAF payments through fintech in the millennial era.Implications – National Board of Zakat (Badan Amil Zakat Nasional, BAZNAS) and Amil Zakat Institution (Lembaga Amil Zakat, LAZ) must promote their goods in connection to ZISWAF payments on a predefined digital platform and a way to get millennials interested in ZISWAF via fintech.Originality – This study uses the collaboration theory of TPB and UTAUT, so not many use it, especially in research on public perceptions of paying ZISWAF through fintech.